Components of Mathematics Anxiety: Factor Modeling of the MARS30-Brief - Pletzer, Belinda; Wood, Guilherme; Scherndl, Thomas; Kerschbaum, Hubert H.; Nuerk, Hans-Christoph (Frontiers in Psychology, 2016)
Mathematics anxiety involves feelings of tension, discomfort, high arousal and physiological reactivity interfering with number manipulation and mathematical problem solving. Several factor analytic models indicate that mathematics anxiety is rather a multidimensional than unique construct. However, the factor structure of mathematics anxiety has not been fully clarified by now. This issue shall be addressed in the current study. The Mathematics Anxiety Rating Scale (MARS) is a reliable measure of mathematics anxiety (Richardson & Suinn, 1972), for which several reduced forms have been developed. Most recently, a shortened version of the MARS (MARS30-brief) with comparable reliability was published. Different studies suggest that mathematics anxiety involves up to seven different factors. Here we examined the factor structure of the MARS30-brief by means of confirmatory factor analysis. The best model fit was obtained by a six-factor model, dismembering the known two general factors “Mathematical Test Anxiety” (MTA) and “Numerical Anxiety” (NA) in 3 factors each. However, a more parsimonious 5-factor model with 2 sub-factors for MTA and 3 for NA fitted the data comparably well. Factors were differentially susceptible to sex differences and differences between majors. Measurement Invariance for sex was established.